La revolución del grafeno en la construcción y desarrollo de células (2016)
With the development of new and more advanced technologies, it also increases the demand for sources or raw materials more used with which we have had for many centuries. This is the case of lead, graphite, silicon, chromium, among others. Overexploitation of this type of raw material has become a problem not only due to the scarcity of the product, but also by pollution and damage caused to the environment. Humans seek wellness, no matter the cost, but in recent times it is remarkable the special interest in products that are more expensive, not only raw materials, also in production, such as silicon, used in the production photovoltaic cells. High production costs have resulted in slow development in the use of photovoltaic solar cells. Graphene plays an important role in response to this challenge because it allows to replace its main applications, such as white graphene, which it is postulate already as a solution in oil spills and water purification. In addition, the features of this element give social and economic benefits, which have become a revolutionary element in all types of industries. This article presents the research and technological developments that constitute the beginning of what could become the most important material, and how can be used for the environment.